1C as a platform for cloud computing at the enterprise and universities - M. P. Yemets; D. S. Kobzar (Academy of Cognitive and Natural Sciences, 2014)
The aim of this study is to analyze 1C cloud services functionality. Objectives of the study is to determine the advantages and disadvantages of 1C using cloud technologies. The object of research is the using cloud technology at enterprise and universities. The subject of research is the use of cloud platform 1C:Enterprise for enterprise and universities. This paper discusses the main advantages and disadvantages of cloud technology, the cloud services of 1C are analyzed, the possibilities of its use at enterprises and universities are determined. The study identified specific recommendations for the implementation of cloud-based technology 1C platform.